FUNCTIONAL CAPACITY EVALUATION IN INSTITUTIONALIZED ELDERY IN THE CITY OF JEQUIÉ, STATE OF BAHIA. (Fiep Bulletin - online, 2014)
The aim of this study was to evaluate functional capacity in institutionalized elderly. This is a descriptive exploratory study with quantitative approach. The sample of this study was 60 institutionalized elderly in the city of Jequié, State of Bahia, being inclusion criteria: cognitive conditions to answer the query, voluntary participation and signature of the agreement term. The query had sociodemographic and health variables and Barthel Index. Data showed that 58,3% of the elderly had age between 60 to 80 years, 60% have shoused cognitive changes however they not showed cognitive deficit, 81,7% had bone and muscle pathologies and 73,3% related pain. 70% showed functional capacity decrease, mainly in activities as going upstairs (81,7%) and transfer for intimal hygiene activities (66,7%). Crossing total Barthel score obtained with variables of this study, there was statistical significance in all the variables. Institutionalized elderly need assistance in activities of daily living, what can impair their quality of life.
Keywords: Health of Institutionalized Elderly; Activities of Daily Living; Evaluation